2022
DOI: 10.1007/s12325-022-02179-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Neridronate in the Management of Bone Loss in Patients with Duchenne Muscular Dystrophy: Results from a Pilot Study

Abstract: Introduction Bone loss is a major issue in patients affected by Duchenne muscular dystrophy (DMD), a rare musculoskeletal disorder, particularly in those treated with glucocorticoids (GCs). We aimed to assess the effectiveness of neridronate in terms of bone mineral density (BMD) changes in this population. Methods We retrospectively reviewed the records of patients affected by DMD receiving GCs referred to our outpatient from 2015 to 2020. All patients were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Looking into descriptive results from included observational cohort studies, Nasomyont et al 18 observed a similar prevalence of thoracic and lumbar vertebral fractures at baseline and each year of follow-up (ranging up to 5 years) in 52 US patients treated with oral alendronate; Sbrocchi et al 21 documented 3 incident vertebral fractures in 2 patients across the 2-year follow-up period (corresponding to a mean incidence rate per person-year of 0.30) in 5 Canadian patients treated with IV pamidronate or zoledronate; and Moretti et al 17 recorded no new fractures during follow-up.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Looking into descriptive results from included observational cohort studies, Nasomyont et al 18 observed a similar prevalence of thoracic and lumbar vertebral fractures at baseline and each year of follow-up (ranging up to 5 years) in 52 US patients treated with oral alendronate; Sbrocchi et al 21 documented 3 incident vertebral fractures in 2 patients across the 2-year follow-up period (corresponding to a mean incidence rate per person-year of 0.30) in 5 Canadian patients treated with IV pamidronate or zoledronate; and Moretti et al 17 recorded no new fractures during follow-up.…”
Section: Resultsmentioning
confidence: 85%
“…Individual study samples comprised between 1 and 520 cases, and the age of patients ranged between 5 and 23 years (5 studies did not report minimum and maximum ages). 4 , 13 , 17 , 20 , 22 Two (11%) studies reported results from randomized controlled trials, 24 , 25 8 (42%) from retrospective cohort studies, 4 , 11 , 13 , 17 , 18 , 20 , 21 , 23 5 (26%) from case studies/series, 10 , 14 , 15 , 19 , 27 2 (11%) from prospective cohort studies, 16 , 26 1 (5%) from a case-control trial, 22 and 1 (5%) from an uncontrolled before-and-after trial. 12 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of neridronate has been suggested also in patients with Duchenne Muscular Dystrophy (DMD) receiving glucocorticoids (GCs). In this population, 1-year treatment with IM neridronate (25 mg monthly), seems to counteract the BMD loss and to prevent incident fragility fractures [80].…”
Section: Secondary Osteoporosismentioning
confidence: 97%